Potential Role of Natural Plant Medicine Cyclocarya paliurus in the Treatment of Type 2 Diabetes Mellitus. (27th December 2021) - Wang, Han; Tang, Cheng; Gao, Zezheng; Huang, Yishan; Zhang, Boxun; Wei, Jiahua; Zhao, Linhua; Tong, Xiaolin
Abstract : Type 2 diabetes mellitus (T2DM) is a common chronic metabolic disease that has become increasingly prevalent worldwide. It poses a serious threat to human health and places a considerable burden on global social medical work. To meet the increasing demand for T2DM treatment, research on hypoglycemic drugs is rapidly developing. Cyclocarya paliurus (Batal.) Iljinskaja is a medicinal plant that grows in China. The leaves of C. paliurus contain polysaccharides, triterpenoids, and other chemical components, which have numerous health benefits. Therefore, the use of this plant has attracted extensive attention in the medical community. Over the past few decades, contemporary pharmacological studies on C. paliurus extracts have revealed that it has abundant biological activities. Multiple in vitro and in vivo experiments have shown that C. paliurus extracts are safe and can play a therapeutic role in T2DM through anti-inflammatory and antioxidation activities, and intestinal flora regulation. Its efficacy is closely related to many factors, such as extraction, separation, purification, and modification. Based on summarizing the existing extraction methods, this article further reviews the potential mechanism of C. paliurus extracts in T2DM treatment, and we aimed to provide a reference for future research on natural plant medicine for the prevention and treatment of T2DM and its related complications.